High Risk of Proximal and Local Neoplasms in 2206 Patients With Anogenital Extramammary Paget's Disease. Issue 11 (November 2019) - Lee, Grace C.; Kunitake, Hiroko; Stafford, Caitlin; Bordeianou, Liliana G.; Francone, Todd D.; Ricciardi, Rocco
Abstract : BACKGROUND: Extramammary Paget's disease is an uncommon intraepidermal adenocarcinoma with poorly defined clinical implications. OBJECTIVE: The purpose of this research was to estimate the risk of second primary neoplasms in patients with extramammary Paget's disease. DESIGN: This was a retrospective analysis of the Surveillance, Epidemiology, and End Results Registry (1973–2014). SETTINGS: The study included population-based cancer registries from the United States. PATIENTS: Patients who were diagnosed with anogenital Paget's disease were included. MAIN OUTCOME MEASURES: Risk of second primary development was measured. RESULTS: We identified 108 patients with anal Paget's disease, 421 patients with male genital (scrotum or penis) Paget's, and 1677 patients with female genital (vagina or vulva) Paget's. Median follow-up time was 5.9 years. The risk of developing colorectal adenocarcinoma was 18.5% for patients with anal Paget's disease. Eighty percent of colorectal adenocarcinoma diagnoses were synchronous (within 2 mo) to anal Paget's diagnoses, whereas metachronous tumors occurred at a median time of 2.4 years. Of patients with anal Paget's disease, 8.3% developed an anal adenocarcinoma or nonsmall cell cancer. In male patients with genital Paget's, the risk of proximal genitourinary malignancy was 9.7%, scrotal or testicular adenocarcinoma was 0.4%, and penile or scrotal squamous carcinoma was 1.7%. In female patients with genital Paget's, the risk of proximal genitourinary malignancy was 3.0%, vaginal or vulvar adenocarcinoma was 1.4%, and vaginal or vulvar squamous neoplasm was 1.0%. Five-year overall survival was 59.7%, 73.5%, and 80.7% in patients with anal, male genital, and female genital Paget's ( p < 0.001). LIMITATIONS: The registry did not record surveillance schedule, provider specialty, or nonprocedural therapies for extramammary Paget's disease. CONCLUSIONS: In the largest published cohort of patients with extramammary Paget's disease, patients with anal Paget's had a much higher risk of both proximal and local neoplasms as compared with patients with genital Paget's. Patients with anal Paget's also experienced worse survival as compared with those with purely genital Paget's. See Video Abstract at http://links.lww.com/DCR/B20 . ALTO RIESGO DE NEOPLASIAS PROXIMALES Y LOCALES EN 2206 PACIENTES CON ENFERMEDAD DE PAGET EXTRAMAMARIA ANOGENITAL: ANTECEDENTES: La enfermedad de Paget extramamaria es un adenocarcinoma intraepidérmico poco frecuente con implicaciones clínicas poco definidas. OBJETIVO: Estimar el riesgo de segundas neoplasias primarias en pacientes con enfermedad de Paget extramamaria. DISEÑO: Análisis retrospectivo del Registro de Vigilancia, Epidemiología y Resultados Finales (1973–2014). LUGAR: Registros de base poblacional en cáncer de los Estados Unidos. PACIENTES: Pacientes que fueron diagnosticados con enfermedad de Paget anogenital. PRINCIPALES MEDIDAS DE RESULTADOS: Riesgo de desarrollo un cáncer primario adicional. RESULTADOS: Se identificaron 108 pacientes con Paget anal, 421 pacientes con Paget genital masculino (escroto o pene) y 1677 pacientes con Paget genital femenino (vagina o vulva). Tiempo mediano de seguimiento fue de 5, 9 años. El riesgo de desarrollar adenocarcinoma colorrectal fue del 18, 5% para los pacientes con Paget anal. El ochenta por ciento de los diagnósticos de adenocarcinoma colorrectal fueron sincrónicos (dentro de los 2 meses) a los diagnósticos de Paget anal, mientras que los tumores metacrónicos ocurrieron en un tiempo promedio de 2, 4 años. De los pacientes con Paget anal, el 8.3% desarrolló un adenocarcinoma anal o cáncer de células no pequeñas. En los pacientes masculinos con Paget genital, el riesgo de malignidad genitourinaria proximal fue del 9, 7%, el adenocarcinoma escrotal o testicular fue del 0, 4% y el carcinoma escamoso del pene o escroto fue del 1, 7%. En pacientes femeninas con Paget genital, el riesgo de malignidad genitourinaria proximal fue de 3.0%, el adenocarcinoma vaginal o vulvar fue de 1.4% y la neoplasia escamosa vaginal o vulvar fue de 1.0%. La supervivencia general a cinco años fue del 59.7%, 73.5% y 80.7% en pacientes con anal, genital masculino y genital femenino, respectivamente (p <0.001). LIMITACIONES: El registro no señalo el cronograma de vigilancia, la especialidad del proveedor o las terapias sin procedimiento para la enfermedad de Paget extramamaria. CONCLUSIONES: En la cohorte más grande publicada de pacientes con enfermedad de Paget extramamaria, los pacientes con Paget anal demostraron un riesgo mucho mayor de neoplasias proximales y locales en comparación con los pacientes con Paget genital. Los pacientes con Paget anal además demostraron una peor supervivencia en comparación con aquellos con Paget aislada genital. Vea el Resumen del Video en http://links.lww.com/DCR/B20 . Abstract : Supplemental Digital Content is available in the text.